Chronic Kidney Disease: Current State of the Problem - M. M. Batiushin (Рациональная фармакотерапия в кардиологии, 2020)
Chronic kidney disease (CKD) is characterized by increasing prevalence, catalyzing properties in relation to cardiovascular and general mortality, and, in most cases, is asymptomatic, which means late diagnostic verifiability. The global average prevalence of CKD is 13.4%, and CKD C3-5 is 10.6%. The main causes of CKD C5 are diabetes mellitus (DM, 46.9%), hypertension (28.8%) and to a lesser extent, glomerulonephritis (7.1%) and polycystic diseases (2.8%), while other causes account for a total of 14.4%. Despite the simple diagnosis of CKD, one of the key problems of modern therapeutic and pediatric clinics is its low detection rate at the early stages, which, according to some data, reaches 96.6%. This review provides data on the criteria for the diagnosis of CKD, as well as more detailed consideration of the course of CKD in patients with DM, hypertension, and heart failure. Attention is paid to the medicinal origin of CKD, as well as to the development of anxiety and depressive disorders in CKD. General issues of treatment of patients with CKD are considered in detail. Lifestyle changes are an important part of the fight against the development and progression of CKD. Currently, Smoking, alcohol, and physical inactivity have been shown to have a harmful effect on the risk of developing and progressing CKD. Diet plays a certain preventive role. The main drugs with nephroprotective properties are angiotensin-converting enzyme inhibitors and angiotensin II receptor antagonists. Both classes of drugs are effective in proteinuric forms of nephropathies and in combination/association of CKD with diabetes or hypertension. The review also provides data on the nephroprotective properties of mineralocorticoid receptor antagonists, endothelin receptor antagonists, and sodium-glucose co-transporter-2 inhibitors. Given the high importance of identifying and effectively treating patients with CKD, it is necessary to focus on early detection of CKD, especially in high-risk groups. It is necessary to raise public awareness by creating and implementing programs for primary prevention of CKD, as well as awareness of patients, motivating them to follow the doctor's recommendations for a long time, including as part of the implementation of a non-drug strategy to combat CKD. It is important to use the full range of methods of drug therapy for CKD, including measures of universal nephroprotection. It should be remembered that the cost of late diagnosis of CKD is a reduction in life expectancy, primarily due to high rates of cardiovascular mortality, disability, and high-cost medication and kidney replacement therapy.